Evaluation Of The Impact Of Innovation And Innovation Management On Competitive Advantage In The Context Of Strategic Management: A Focus On Algeria's Innovation Landscape - Boukrouh Abdallah (جامعة الوادي University of Eloued, 2024)
This study investigates the critical interplay betweeninnovation management, and competitive advantage within the framework of strategic management. Byfocusing on Algeria's unique innovation landscape, we aim to gain insights into the country's strengths and weaknesses in fostering innovation-driven economic growth. Adopting a mixed-method approach, we conducted a thorough literature review to establish the theoretical foundation, and empirical data from the Global Innovation Index was collected to assess Algeria's performance in innovation dimensions and indicators. Our findings underscore the significance of human capital and research as Algeria's strengths, while market sophistication emerged as a key area for improvement. This research contributes to a deeper understanding of the factors influencing competitive advantage through innovation.
Keywords: Strategic Management; Innovation; Innovation Management; Competitive Advantage; Algeria's innovation ecosystem